Respuesta :

Answer:

y = - 2x + [tex]\frac{7}{6}[/tex]

Step-by-step explanation:

The equation of a line in slope- intercept form is

y = mx + c ( m is the slope and c the y- intercept )

Given

y - [tex]\frac{2}{3}[/tex] = - 2(x - [tex]\frac{1}{4}[/tex] ) ← distribute

y - [tex]\frac{2}{3}[/tex] = - 2x + [tex]\frac{1}{2}[/tex]

Add [tex]\frac{2}{3}[/tex] to both sides

y = - 2x + [tex]\frac{1}{2}[/tex] + [tex]\frac{2}{3}[/tex], that is

y = - 2x + [tex]\frac{7}{6}[/tex] ← in slope- intercept form

Answer:b

Step-by-step explanation:

For the lazy ppl .